MAKNA TUTURAN KODA GETO DALAM RITUAL PERKAWINAN MASYARAKAT LAMAWALANG KABUPATEN FLORES TIMUR - Waleng Lureng, Selviana; Lemba, Vinsensius; Wai Lawet, Pilipus (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to describe the meaning of the utterances of the geto code in the marriages of the Lamawalang community, East Flores district. This research method uses qualitative methods. The research data were obtained from informants in the form of traditional expressions of koda geto marriage. From the research results, it can be concluded that the meaning of koda geto utterances in marriage rituals: (1) The meaning of respect, is the giving of respect and appreciation to the male party to the woman, (2) The meaning of cultural preservation, is the meaning of the expression in a traditional speech of koda geto, ( 3) Social meaning, which is related to social relations between one family and another in the koda geto custom, (4) The meaning of unity, which is closely related to establishing trust, togetherness, and having a sense of complementarity between tribes, (5) The meaning of tolerance, In traditional marriages, a harmonious life is always created, namely trying to carry out tolerance between tribes, and (6) The meaning of happiness, in Lamawalang traditional marriages, is if the woman's family accepts the arrival of the male party well.